2021
DOI: 10.3390/s21227475
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Machine Learning-Based Multi-Model Voting Ensemble Methods for Network Threat Detection in Agriculture 4.0

Abstract: The upcoming agricultural revolution, known as Agriculture 4.0, integrates cutting-edge Information and Communication Technologies in existing operations. Various cyber threats related to the aforementioned integration have attracted increasing interest from security researchers. Network traffic analysis and classification based on Machine Learning (ML) methodologies can play a vital role in tackling such threats. Towards this direction, this research work presents and evaluates different ML classifiers for ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The workflow diagram of the stacking ensemble model is depicted in Figure 6 . Voting: The voting classifier in machine learning uses an ensemble of multiple models to forecast an output (class) based on the chance that the result will fall into one of the specified classes [ 38 ]. Using the most popular class as a starting point, this classifier predicts the output class based on an average of all the classifiers that have been submitted to it.…”
Section: Methodsmentioning
confidence: 99%
“…The workflow diagram of the stacking ensemble model is depicted in Figure 6 . Voting: The voting classifier in machine learning uses an ensemble of multiple models to forecast an output (class) based on the chance that the result will fall into one of the specified classes [ 38 ]. Using the most popular class as a starting point, this classifier predicts the output class based on an average of all the classifiers that have been submitted to it.…”
Section: Methodsmentioning
confidence: 99%
“…In hard voting, the final prediction is the class that acquires the most voting from the classifiers. In contrast, in soft voting, the predicted class is the class that achieves the highest average of probability assigned to it by the classifiers [ 43 ]. In this study, the hard voting approach is used, as shown in Equation ( 18 ), where is the final prediction, C i are the predictions of i th observations, and x is the data sample [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…SVM uses a hyperplane to divide the positive and negative samples. The selection of the hyperplane is shown in Figure 3 , which can be described as [ 30 ] where denotes the normal vector, and b indicates the distance between the plane and coordinate origin.…”
Section: Ai-based Discriminant Algorithmsmentioning
confidence: 99%